2004
DOI: 10.1002/lt.20097
|View full text |Cite
|
Sign up to set email alerts
|

The role and limitation of living donor liver transplantation for hepatocellular carcinoma

Abstract: Liver transplantation for hepatocellular carcinoma (HCC) is restricted by the scarcity of cadaver grafts. Living donor liver transplantation (LDLT) may potentially increase the applicability but its role and limitation are not clear. We studied the outcome of a cohort of 51 patients with unresectable HCC who were accepted on list for both options of deceased donor liver transplantation (DDLT) and LDLT. Twenty-five of 51 (49%) patients had voluntary living donors (group 1) and 26 did not (group 2). Patients in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(90 citation statements)
references
References 24 publications
3
85
1
1
Order By: Relevance
“…37 This has to be interpreted with current opinions 37,38 and local results. 39 Continuity of care by the same team of surgeons is logical. 40 Donor feasibility has to be made in concert with the physical condition of the recipient in terms of graft size for recipients with portal hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…37 This has to be interpreted with current opinions 37,38 and local results. 39 Continuity of care by the same team of surgeons is logical. 40 Donor feasibility has to be made in concert with the physical condition of the recipient in terms of graft size for recipients with portal hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…The role of LDLT and its intention-to-treat survival benefit over DDLT in patients with early HCC have been confirmed in clinical series [53], but several observations have emerged that warrant caution in assuming that the advantage of LDLT is as predicted by hypothetical studies. First, the process of waiting for a living donor is comparable with that of waiting for a deceased donor graft.…”
Section: Ldltmentioning
confidence: 99%
“…While the availability of a deceased donor graft depends on a system of organ allocation, the availability of a living donor depends on the family members' voluntarism and the donor selection criteria. A clinical series from Hong Kong showed that Ͼ50% of patients with early HCC might not have a suitable voluntary donor [53]. Second, several recent studies have reported a tendency toward a higher rate of recurrence and lower rate of survival after LDLT for HCC.…”
Section: Ldltmentioning
confidence: 99%
“…7,8 This pressure has driven the increased use of living and marginal donors as well as split cadaveric transplantations. [9][10][11][12] Also of concern is whether any increase in tumor burden, even below the current limits warranting removal from transplant candidacy, might adversely affect posttransplantation prognosis.…”
mentioning
confidence: 99%